(untitled) (Semiárida, 2018)
Since 2006, we began to observe in the caldén forest of La Pampa province the bagworm presence. For this reason we set as our objectives to study how plants are feeding the O. platensis larvae in the caldén forest and to detect parasitoids that may be affected in the study area. These skills are critical to then implement a strategy for pest management that includes actions to promote the increase of native parasitoids that may biologically control this species pest and protect the Federal Reserve vegetation. The field work was carried out in the Reserva Natural Provincial Parque Luro, located on Ruta Nacional N º 35, km 292 - Toay, Province of La Pampa. This Nature Reserve is a protected area that conserves Caldén Forest at 7600 ha, of which 1600 of them are destined to tourism and recreation. It is located in the phytogeographic region of El Espinal, forest dominated by a legume, the caldén. We collected a total of 1365 bags which were taken to the laboratory for examination. It was noted that 47% were unoccupied, 19% were male and 32% were female bags. New host are cited for O. platensis in a caldén forest in La Pampa province. These hosts are the following native plants: Prosopis caldenia (Burk.) "Caldén", Condalia microphylla Cav. "Piquillín", Jodina rhombifolia (Hook. & Arn.) "Sombra de toro", Schinus fasciculatus var. arenicola (Hauman) F. A. Barkley “Molle”, Aloysia gratissima (Gill. & Hook) "Azahar del monte”. It was not observed recolonization, after one year, in the marked trees. In this work 6 genera of hymenpterous parasitoids were reared either from the bagworms represented by five families of Hymenoptera: Tetrastichus sp. (Hymenoptera: Eulophidae), Chirotica bruchii (Breth, 1904) (Hymenoptera: Ichneumonidae), Conura sp.1 (Hymenoptera: Chalcididae), Conura sp. 2 (Hymenoptera: Chalcididae), Perissocentrus sp. (Hymenoptera: Torymidae) and Chelonus (Hymenoptera: Braconidae). This research provides initial information required that may contribute to the establishment of an Integrated Pest Management Program in the Reserve.